Cerebrospinal fluid cannot be used to distinguish inflammatory myelitis from congestive myelopathy due to spinal dural arteriovenous fistula: case series. Issue 1 (22nd December 2019) - Vivekanandam, Vinojini; Li, Vivien; Wu, Teddy; Dowling, Richard; Roxburgh, Richard H; McGuiness, Ben J; Kilfoyle, Dean H; Manji, Hadi; Quaegebeur, Annelies; Thom, Maria; Robertson, Fergus; Thevathasan, Wesley; et al.
Abstract : Patients with congestive myelopathy due to spinal dural arteriovenous fistula (SDAVF) typically present with progressive sensory and motor disturbance in association with sphincter dysfunction. Spinal MRI usually shows longitudinally extensive T2 signal change. Here, we report four patients with progressive myelopathy due to SDAVF who also presented with findings on cerebrospinal fluid (CSF) examination suggestive of an inflammatory aetiology. Such CSF findings in SDAVF are important to recognise, to avoid the erroneous diagnosis of an inflammatory myelitis and inappropriate treatment with immunosuppression. SDAVF can be difficult to detect and may require repeated investigation, with formal angiography as the gold standard.